3D bioprinting : fundamentals, principles and applications - Ozbolat, Ibrahim Tarik, 1983- (Elsevier, AP, 2017)
"This book provides the latest information on the fundamentals, principles, physics, and applications of 3D bioprinting. It contains descriptions of the various bioprinting processes and technologies used in additive biomanufacturing of tissue constructs, tissues, and organs using living cells."--Resumé vydavatele
Keywords: bioinženýrství; trojrozměrný tisk; trojrozměrné zobrazování; bioengineering; three-dimensional printing; three-dimensional imaging; příručky; handbooks and manuals